EFFECT OF CHITRAKADI GHRITAM IN THE MANAGEMENT OF VANDHYATVA (INFERTILITY) WITH YONIDOSHA - Subbalakshmi, Bhaskaruni; Madhukar Paranjape, Meera (International Journal of Ayurveda and Pharma Research, 2015)
Reproduction is the noblest and most reverent of all human powers. God has given this precious gift to the woman. Motherhood is the cherished desire deep down in the heart of every woman. Failure to achieve conception is known as Vandhyatva (Infertility). Even in the computer age, it is estimated that nearly 10-15% of couples are infertile in India. The ancient system of Ayurvedic medicine advocated variety of medication, which provides good results without any harmful effect. The main causes of infertility are tubal block, PCOD, PID and endometriosis. The drug Chitrakadi ghrita was selected which Sushruta mentioned in the management of Vandhya. The Chitrakadi ghrita was given in the dose of 10gm once in a day empty stomach at 6 am with 100ml of lukewarm water for the duration of 3 months with the result assessment recorded at every 1 month. It proved that Chitrakaadi ghrita is very effective in management of Vandhyatva with Yonidosha.